A Validated, Rapid and Cost-Efficient HPTLC Method for Quantification of Gamma-Linolenic Acid in Borage Oil and Evaluation of Antioxidant Activity. (3rd June 2021) - Kawish, S M; Qadir, Abdul; Saad, Suma; Beg, Sarwar; Jain, Gaurav K; Aqil, Mohd; Alanazi, Amer M; Khan, Azmat Ali; Rashid, Md Abdur; Rab, Rehan A; Almalki, Waleed H; Ahmad, Farhan J
Abstract: Borage oil that is extracted from ( Borago officinalis Linn.) is a well-known medicinal plant having various medicinal benefits. In this work, an affordable, simple, reliable, rapid and easily accessible high-performance thin-layer chromatography (HPTLC) method was developed for the estimation of gamma-linolenic acid (GLA) in borage oil. HPTLC method employs thin-layer chromatography (TLC) aluminum plates precoated with silica gel (G60F254) as the stationary phase, and the mixture of hexane:toulene:glacial acetic acid (3:7:1, v/v/v) was used as the mobile phase. Densitometric analysis of the TLC plates was carried out at 200 nm. The developed method showed well-resolved spots with retention factor ( R f ) value of 0.53 ± 0.04 for GLA. Various experimental conditions like saturation time for chamber, solvent phase migration and width of the band were studied intensely for selecting the optimum conditions. The method validation was performed for parameters like linearity, accuracy, specificity and precision. The values of limit of detection and limit of quantification for GLA were found to be 0.221 and 0.737 μg/band, respectively. In nutshell, the developed HPTLC method was found to be highly sensitive for the estimation of GLA in the herbal oil samples and formulations.